2008
DOI: 10.1109/tns.2008.922827
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Concepts of Photonic Crystals on Scintillating Materials

Abstract: Abstract-The high refractive index of current scintillating materials puts severe restrictions on their effective light yield. In this paper, we describe an approach that uses a photonic crystal pattern machined into the coupling face of the scintillator to partly overcome the problem of total internal reflection. Simulations are performed for 2 mm 2 mm 8 mm LuAP and LSO pixels with and without photonic crystal and different types of wrapping. It is shown that by tuning the structure of the photonic crystal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…For crystals with high aspect ratios, as the ones used in PET scanners, up to 50% of the scintillation light will not be collected [28], even if Teflon wrapping and optical coupling are used, and a large fraction of the collected photons will be delayed by multiple bouncings in the crystal. Several years ago, we proposed to use photonic crystal slabs (PhC slabs), defined as thin dielectric layers structured with a 2D or 3D periodic pattern, to increase this efficiency [29]. A higher light output, combined with a reduction of the average path length of the photons in the crystal before their extraction, leads to a better energy and time resolution.…”
Section: Rationale For Photonic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For crystals with high aspect ratios, as the ones used in PET scanners, up to 50% of the scintillation light will not be collected [28], even if Teflon wrapping and optical coupling are used, and a large fraction of the collected photons will be delayed by multiple bouncings in the crystal. Several years ago, we proposed to use photonic crystal slabs (PhC slabs), defined as thin dielectric layers structured with a 2D or 3D periodic pattern, to increase this efficiency [29]. A higher light output, combined with a reduction of the average path length of the photons in the crystal before their extraction, leads to a better energy and time resolution.…”
Section: Rationale For Photonic Crystalsmentioning
confidence: 99%
“…The idea of introducing photonic crystals to increase the performance of scintillating crystals used in ionizing radiation detection had been first introduced in 2008 [29]. The first goal was to overcome the problem of light extraction and light coupling inefficiencies from the crystal to the photodetector because of the high refractive index mismatch between the crystal (generally high) and the out-coupling medium (generally low).…”
Section: Perspectivesmentioning
confidence: 99%
“…This not only leads to a reduction of light collected at the photo detector, with consequences on the photo statistics described above, but also to multiple light reflections within the scintillator, which can contribute as much as 150 ps FWHM in a 2 2 20 mm LSO pixel. A possible solution to overcome the problem of total internal reflection is to improve the light extraction efficiency at the crystal/photo detector interface by means of photonic crystals (PhCs), i.e., media with a periodic modulation of the dielectric constant [12], [13]. Fig.…”
Section: Light Transportmentioning
confidence: 99%
“…EVERAL years ago, we identified photonic crystals (PhCs) as a tool with a high potential to significantly improve the performance of scintillator-based detectors [1], [2]. We have shown that well-designed PhCs can enhance the light output of dense scintillators with a high refractive index (between 1.8 and 2.2 for the majority of scintillators) by a large factor ( 2 in air and by at least 50% in grease) [3], [4].…”
mentioning
confidence: 99%
“…As a consequence, PhCs can offer attractive perspectives in the search for higher timing resolution in scintillator-based detectors [5]. Increasing the light output and, as a consequence, the rate of photoelectrons produced in the photodetector at the early stage of the signal generation has a direct impact on the timing resolution by virtue of the improved photostatistics as illustrated by the following formula derived from Hyman theory: (1) where is the scintillator decay time, is the number of photoelectrons and is the excess noise factor of the photodetector.…”
mentioning
confidence: 99%